SAJADAH TERAKHIR KARYA EDY A EFFENDI: SEBUAH ANALISIS SEMIOTIK MICHAEL RIFATERRE - Al-Hafizh, Muhammad. (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
The feeling of loneliness to find the turning point in life is the great motivation for noble creatures to meet the Lord. It is started from the awareness toward the hazardous of unsatisfying life which is full of hedonisms.Â  Someone only can get a real satisfaction in his life when God blesses him, when he realizes that God is near. Human should keep struggle to gain such life. Edy A Effendyâ€™s Sajadah Terakhir reflects the hard effort of human being to get close to his Lord. Many symbols which are used in this poem, and it becomes a mystery that should be revealed. Those symbols are used to describe the struggle of human to meet his God. This article is aimed at revealing the meaning of this poetry and getting the meaning behind the words by using the semiotics concept of Michael Rifaterre. It will be done through four steps; heuristics reading, hermeneutics reading, finding matrix model and variant, and finally is hypo gram.Â